2013
DOI: 10.1017/s1092852913000655
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of selegiline transdermal system (STS) for the atypical subtype of major depressive disorder: pooled analysis of 5 short-term, placebo-controlled trials

Abstract: STS appears to be comparably efficacious and tolerable in atypical and nonatypical subtypes of MDD. Adequately powered, controlled, clinical trials are necessary to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“… 11 In the GENDEP study, there was no indication that AD may respond better to SSRI than to tricyclic antidepressants as a similar efficacy of escitalopram and nortriptyline was observed. 37 Pae et al 76 in a post hoc analysis of five short-term trials with selegiline (selective MAOI type B) showed equal efficacy of this drug in patients with atypical and non-atypical subtype of depression.…”
Section: Treatmentmentioning
confidence: 99%
“… 11 In the GENDEP study, there was no indication that AD may respond better to SSRI than to tricyclic antidepressants as a similar efficacy of escitalopram and nortriptyline was observed. 37 Pae et al 76 in a post hoc analysis of five short-term trials with selegiline (selective MAOI type B) showed equal efficacy of this drug in patients with atypical and non-atypical subtype of depression.…”
Section: Treatmentmentioning
confidence: 99%
“…Reversible inhibitors such as moclobemide and toloxatone, on the other hand, represent safer and better-tolerated MAO-A inhibitors [14,15]. A transdermal delivery system of the MAO-B selective inhibitor, (R)-deprenyl (selegiline), has also been shown to be effective in the treatment of major depressive disorder in clinical trials [16]. Since this formulation does not lead to the inhibition of MAO-A in the gastrointestinal and hepatic systems, the risk of tyramine-induced hypertension is low.…”
Section: Introductionmentioning
confidence: 99%
“…Both reversible and irreversible inhibitors of MAO-B, on the other hand, do not cause tyramine-induced changes in blood pressure and these agents have good safety profiles[16]. To investigate the reversibility of MAO inhibition by the 1,4-benzoquinones, mixtures containing the MAO enzymes and test inhibitors were incubated for 15 min and subsequently dialysed for 24 h[39].…”
mentioning
confidence: 99%
“…EMSAM was equally efficacious in atypical and non-atypical depressives. 76 Whether EMSAM is more effective than non-MAOI antidepressants for atypical depression should be assessed. Nonetheless, these recent findings should provide clinicians at least a sense of confidence in administering EMSAM to patients with MDD since atypical depression did not have a negative influence on treatment response.…”
Section: Failure To Point Out Potential Advantages Of Emsam Over Othementioning
confidence: 99%